Tracking The Mastery of Social Interpreters’ Knowledge of Religious Activities In Indionesia - Febrina Tobing; Rudy Sofyan; Syahron Lubis; Umar Mono (English Language and Literature International Conference (ELLiC) Proceedings, 2023)
This research was concerned with social consecutive interpreting; its objetive was to analyze and find out the mastery in knowledge of two interpreters who played their role in two different religious activities. The first religious activities led by an American Evangelist, namely John Hartman; and the other activities led by the Israeli Evangelist, namely Ps. Benny Hinn. Both the Interpreters observed in this research are Indonesian and work as an Evangelist. The data in this research were collected by using questionnaire and conducting interviews and processed by using Likert scale calculation and analyzed by using descriptive quaitative method, based on the theory of interpreting competency in order to find out their mastery in knowledge to determine their competency in interpreting. The questionnaire then given to three raters who are Indonesian and really experienced in doing Interpreting in religious setting. The result of this research are: (i) both Interpreters mastered in both source and target language (namely English and Indonesia), as well as in both cultures; (ii) although they do not work as an Interpreter, both of them are succeed in transferring the message and making the audiences understand about the preaching.